Forced Oscillations of Half-Linear Elliptic Equations via Picone-Type Inequality - Norio Yoshida (International Journal of Differential Equations)
Picone-type inequality is established for a class of half-linear elliptic equations with forcing term, and oscillation results are derived on the basis of the Picone-type inequality. Our approach is to reduce the multi-dimensional oscillation problems to one-dimensional oscillation problems for ordinary half-linear differential equations.